Factors Affecting the Application of the International Extensible Business Reporting Language (XBRL) in Palestine Exchange's Listed Companies - SOLAIMAN ABOU MUSTAPHA, MOHAMED MUSTAPHA (Journal of Research in Finance and Accounting, 2020)
The study aimed at determining the impact of each of the following factors and variables : company size, profitability of the company, liquidity of the company, the sector to which the company belongs, age of the company, level of independence of the Board of Directors of the company, size of indebtedness of the company, private or public sector), on applying the International Extensible Business Reporting Language (XBRL) in Palestine Exchange's listed companies. The study followed the descriptive analytical method. The study concluded that there are a number of factors that affect the application of (XBRL), most importantly that wherever the volume of company operation increased, the profit increased, liquidity raised, age increased, the independency of the company Board of Directors increased and its debit decreased, the ability of the company to apply (XBRL) increased .